2013
DOI: 10.1007/s11302-013-9372-5
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signalling and cancer

Abstract: Receptors for extracellular nucleotides are widely expressed by mammalian cells. They mediate a large array of responses ranging from growth stimulation to apoptosis, from chemotaxis to cell differentiation and from nociception to cytokine release, as well as neurotransmission. Pharma industry is involved in the development and clinical testing of drugs selectively targeting the different P1 nucleoside and P2 nucleotide receptor subtypes. As described in detail in the present review, P2 receptors are expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
274
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(285 citation statements)
references
References 699 publications
(387 reference statements)
7
274
1
3
Order By: Relevance
“…The most probable candidate channels for Ca 2ϩ influx are P2Xs, because P2Xs per se are Ca 2ϩ -permeable cation channels (31). As discussed earlier, H23 and A549 lung cancer cells had significantly higher levels of P2X 3 , P2X 4 , and P2X 5 expression compared with normal cells. Studies have shown that P2X receptors desensitize ATP fast and mediate short-time inward current (36), which may underlie the limited Ca 2ϩ influx induced by the activation of P2X receptors shown in P2X inhibitor and agonist data.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The most probable candidate channels for Ca 2ϩ influx are P2Xs, because P2Xs per se are Ca 2ϩ -permeable cation channels (31). As discussed earlier, H23 and A549 lung cancer cells had significantly higher levels of P2X 3 , P2X 4 , and P2X 5 expression compared with normal cells. Studies have shown that P2X receptors desensitize ATP fast and mediate short-time inward current (36), which may underlie the limited Ca 2ϩ influx induced by the activation of P2X receptors shown in P2X inhibitor and agonist data.…”
Section: Discussionsupporting
confidence: 59%
“…ATP, well known as an intracellular molecular energy source, also functions as an extracellular messenger (2). ATP receptors are purinergic receptors (P2 receptors) and include the ligand-gated ion channel family of P2 receptors (P2X1-7) as well as the G protein-coupled receptor (GPCR) family of P2 receptors (P2Y1-2, P2Y 4 , P2Y 6 and P2Y11-14) (3,31). Activation of P2X receptors, which are nonselective cation channels formed by three homomeric or heteromeric P2X subunits, directly results in Na ϩ and Ca 2ϩ influx through the cell plasma membrane, leading to membrane depolarization, which in turn activates voltage-gated Na ϩ and Ca 2ϩ channels and causes the firing of action potentials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most tumors express P2X7R to high level, and are dependent on its function for growth and metastatization (4,41). In tumor cells, P2X7R is constantly and tonically active, thus causing: (i) moderate increase in the endoplasmic reticulum and mitochondrial Ca 2þ concentration; (ii) enhanced efficiency of oxidative phosphorylation; (iii) increase in intracellular ATP stores; (iv) activation of the transcription factor NFATc1; (v) stimulation of aerobic glycolysis; and (vi) stimulation of proliferation (5,38,40,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…P2 receptors are classified into two subfamilies, ionotropic P2X1-7 receptors and metabotropic P2Y1-14 receptors, and their activation regulates many physiological functions [8]. P2 receptors are also expressed in many types of cancer [9]. Among these molecules, P2X7 receptor shows increased expression in many types of cancer cells [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%